STUDI KEPATUHAN WAJIB PAJAK DARI ASPEK PENGETAHUAI PERSEPSI, DAN SISTEM ADMINISTRASI - Asih, Devi Tri; Salman, Kautsar Riza (Universitas Hayam Wuruk Perbanas, 2011)
The low level of tax compliance and tax reform in tax administration system are considered the two important issues. This importonce has become the background of this research. This research is expected to be able to answer what factors can affect the level of tax compliance. The variables used in this study include: lorcwledge of tax, the perception of 'fiscus